Structure and function of the enhancer 3' to the human A gamma globin gene. - Purucker, M (1990)
An enhancer is located immediately 3' to the A gamma globin gene. We have used DNase I footprinting to map the sites of interaction of nuclear proteins with the DNA sequences of this enhancer. Eight footprints were discovered, distributed over 600 base pairs of DNA. Three of these contain a consensus binding site for the erythroid specific factor GATA-I. Each of these GATA-1 sites had an enhancer activity when inserted into a reporter plasmid and tested in human erythroleukemia cells. Other footprints within the enhancer contained consensus binding sequences for the ubiquitous, positive regulatory proteins AP2 and CBP-1. An Sp1-like recognition sequence was also identified. Synthetic oligonucleotides encompassing two of the footprints generated a slowly migrating complex in gel mobility shift assays. The same complex forms on a fragment of the human gamma globin gene promoter extending from -260 to -200. The DNaseI footprint of this protein complex with the enhancer overlapped a sequence, AGGAGGA, found within the binding site for a protein that interacts with the chicken beta globin promoter and enhancer, termed the stage selector element. We propose that this complex of proteins may be involved in the human gamma globin promoter-enhancer interaction.